1960
DOI: 10.1017/s0021859600022619
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the production of beef from zebu cattle in East Africa I. A description of the Muguga herd

Abstract: 1. The formation of a herd of Northern Frontier Zebus for genetical research has been described.2. Details are given of the system of mating used and the type of management adopted.Thanks are due to Dr J. W. B. King of the Animal Breeding Research Organization, Edinburgh, for his advice, to Mr M. A. Witcomb for taking the photographs, and to the Directors of the East African Veterinary Research Organization and the East African Agriculture and Forestry Research Organisation for their encouragement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1960
1960
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The general description of the zebu herd, its environment, management and the experimental design has been given by Lampkin & Lampkin (1960), and in the first of these two papers (Carles & Lampkin, 1977).…”
Section: The Experimental Herdmentioning
confidence: 99%
“…The general description of the zebu herd, its environment, management and the experimental design has been given by Lampkin & Lampkin (1960), and in the first of these two papers (Carles & Lampkin, 1977).…”
Section: The Experimental Herdmentioning
confidence: 99%
“…Most of the previously reported assay procedures are based on depolymerization of paraldehyde by acid and heat to its monomer, acetaldehyde, which is then measured by gas chromatography with flame ionization detection [13][14][15]. Lampkin [13] reported a GLC method for determination of paraldehyde in pharmaceutical preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Lampkin [13] reported a GLC method for determination of paraldehyde in pharmaceutical preparations. Although the method only involves dilution of the paraldehyde sample prior to analysis of its paraldehyde content, this assay may be unsuitable for analyzing biological samples, which may require clean up before injection onto the chromatograph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing plane of nutrition at fertilization is positively correlated with conception, e.g. Thus, Lampkin, Howard and Burdin (1961) showed that supplementing the diet of phosphorus deficient Zebu cattle in Kenya with dicalcium phosphate showed little improvement in fertility. Many nutritional factors, notably some of the micronutrients involved in energy metabolism or supply -magnesium, iodine -are often implicated as possible causes of infertility (McDowell, 1976).…”
Section: (D) Reproductionmentioning
confidence: 99%